Unveiling the Mechanism of Bulk Spin‐Orbit Torques within Chemically Disordered FexPt1‐x Single Layers. (24th June 2021) - Zhu, Lijun; Ralph, Daniel C.; Buhrman, Robert A.
Abstract: The recent discovery of spin‐orbit torques (SOTs) within magnetic single‐layers has attracted attention. However, it remains elusive as to how to understand and how to tune the SOTs. Here, utilizing the single layers of chemically disordered Fe x Pt1‐ x, the mechanism of the "unexpected" bulk SOTs is unveiled by studying their dependence on the introduction of a controlled vertical composition gradient and temperature. The bulk dampinglike SOT is found to arise from an imbalanced internal spin current that is transversely polarized and independent of the magnetization orientation. The torque can be strong only in the presence of a vertical composition gradient. The SOT efficiency per electric field is insensitive to temperature but changes sign upon reversal of the orientation of the composition gradient, which is analog to the strain behaviors. These characteristics suggest that the imbalanced internal spin current originates from a bulk spin Hall effect and that the associated inversion asymmetry that allows for a non‐zero net torque is most likely a strain non‐uniformity induced by the composition gradient. The fieldlike SOT is a relatively small bulk effect compared to the dampinglike SOT. This study points to the possibility of developing low‐power single‐layer SOT devices by strain engineering. Abstract : Strong "unexpected" bulk spin‐orbit torques are revealed within magnetic single layers of Fe x Pt1‐ x arising from the interplay of an imbalanced transversely polarized spin current generated by a bulk spin Hall effect and broken inversion symmetry due to composition‐gradient induced strain non‐uniformity. This finding points to the possibility of developing low‐power single‐layer spin‐orbit torque devices by strain engineering.